(untitled) (Journal of Pedagogical Inventions and Practices, 2026)
Orthodontic tooth movement induces significant morphological changes in the alveolar bone as a result of controlled mechanical force application. These changes involve coordinated processes of bone resorption and apposition that allow teeth to reposition within the dental arch. Understanding alveolar bone remodeling is critical for achieving stable orthodontic outcomes and preventing complications such as dehiscence, fenestration, and bone loss. The aim of this study was to evaluate morphological alterations of alveolar bone during orthodontic treatment and to assess their clinical implications. A prospective radiographic study of 130 orthodontic patients aged 14–25 years was conducted using cephalometric analysis and cone-beam computed tomography (CBCT). Parameters such as cortical bone thickness, alveolar height, trabecular density, and bone volume were analyzed before and after treatment. The results demonstrate that controlled orthodontic forces stimulate adaptive remodeling of alveolar bone; however, excessive or improperly directed forces may lead to cortical thinning and localized bone defects. These findings emphasize the importance of biomechanical precision and radiographic monitoring during orthodontic therapy.